First Case Report on Quantification of Antimicrobial Use in Corporate Dairy Farms in Pakistan - Umair, Muhammad; Abdullah, Rana Muhammad; Aslam, Bilal; Nawaz, Muhammad Hassan; Ali, Qasim; Fatima, Fariha; Ali, Jabir; Zahoor, Muhammad Asif; Mohsin, Mashkoor (Frontiers in Veterinary Science, 2020)
Intensive livestock farming has become indispensable to meet the rapidly increasing demand for animal-based nutrition in low- and middle-income countries (LMICs) where antimicrobials are frequently used for treatment and prophylactic or metaphylactic purposes. However, very little is known about the trends of antimicrobial use (AMU) in dairy animals in LMICs. The objective of this study was to quantify AMU in two large commercial dairy farms in Pakistan. A retrospective study was conducted at two corporate commercial dairy farms located in Punjab province for the year 2018. AMU was calculated using 3 metrics: active ingredient (kg) and milligrams per population unit (mg/kg), which quantifies the amount of active ingredient used, and antimicrobial treatment incidence (DDDA/1,000 cow-days), which estimates the per day number of treatments to 1,000 cows. Total on-farm AMU was found to be 138.34 kg, 65.88 mg/kg, and 47.71 DDDA/1,000 cow-days. Measured in antimicrobial treatment incidence (ATI) aminoglycosides (11.05 DDDA/1,000 cow-days), penicillins (8.29 DDDA/1,000 cow-days), and tetracyclines (8.1 DDDA/1,000 cow-days) were the most frequently used antimicrobial classes. A total of 42.46% of all the antimicrobials used belonged to the critically important antimicrobials for human medicine as defined by the WHO. Considerably high AMU was found compared to other farm-level studies across the world. This was the first study to quantify AMU in the dairy industry in Pakistan. Our results showed that corporate commercial dairy management practices are associated with increased antimicrobial consumption and highlight the need for antimicrobial stewardship programs to encourage prudent use of antimicrobials in corporate dairy.